Analysis of Cyber Diplomacy and its Challenges for the Digital Era Community - Maulana, Yusril Ihza; Fajar, Irfan (IAIC Transactions on Sustainable Digital Innovation (ITSDI), 2023)
This paper looks at digital strategy and what it can do to promote a peaceful global local area in the age of computers. Cyberspace holds a key position and particular relevance in international affairs. This subject has gained popularity as most international entertainers have developed their global strategy and implemented various tactics to pursue their primary goals online. For instance, the Ministry of Foreign Affairs' use of social media to promote the country, its policies, and its ideals are clear evidence of this. Unfortunately, not all online activities are calm. China and the US are at odds over cyber security, and two groupings of countries are vying for control of the field internationally. Because of this conflict of interest between the countries, cyber diplomacy is required to arbitrate and prevent open cyber war. Cyber diplomacy is an international practice that results from efforts to create an international cyber community by connecting the national interests of nations with the dynamics of the global community. To fulfill the traditional duties of diplomacy in cyberspace, such as promoting trust and peace among stakeholders, cyber diplomacy is to do so. This paper uses English School diplomacy theory to analyze the potential of cyber diplomacy for peaceful cyberspace use. Digital tact consists of two main components: an effort to prevent internet deterioration and a globally coordinated apparatus for creating common digital standards.